2002
DOI: 10.1080/1475636021000010914
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Competitive Inhibitors for the Transferase Activity of Pseudomonas aeruginosa Exotoxin A

Abstract: A series of small, nonpolar compounds were tested for their ability to inhibit the ADP-ribosyl transferase activity of Pseudomonas aeruginosa exotoxin A. The IC50 values for the compounds tested ranged from 87 nM to 484 microM for NAP and CMP12, respectively. It was demonstrated that NAP was a competitive inhibitor of the ADPRT reaction for the NAD+ substrate with a Ki of 45 +/- 5 nM, which was in good agreement with the dissociation constant determined independently (KD = 56 +/- 6 nM). The IC50 value for NAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…We demonstrated previously that NAP is a potent in vitro competitive inhibitor against the NAD + substrate of ExoA c (Armstrong et al , 2002) and, herein, we also show that NAP is an effective in vitro inhibitor of both DT c and cholix c (Table 1). More specifically, NAP mimics the nicotinamide moiety of NAD + and binds into a nonpolar substrate pocket within the enzymes as shown in Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…We demonstrated previously that NAP is a potent in vitro competitive inhibitor against the NAD + substrate of ExoA c (Armstrong et al , 2002) and, herein, we also show that NAP is an effective in vitro inhibitor of both DT c and cholix c (Table 1). More specifically, NAP mimics the nicotinamide moiety of NAD + and binds into a nonpolar substrate pocket within the enzymes as shown in Fig.…”
Section: Resultssupporting
confidence: 81%
“…NAP was previously shown to be a potent inhibitor of ExoA c in vitro mART activity (Armstrong et al , 2002). To determine whether NAP could protect yeast cells expressing DT group mART toxins, yeast broth was supplemented with 50 μM of the inhibitor (in 1% DMSO) before toxin induction with Cu 2+ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1). It was previously demonstrated that the P-series compounds compete with the NAD ϩ substrate in ExoA/cholix by binding within the nicotinamide binding site within these enzymes (2,36). The virtual screen approach identified 72 hits (prospective inhibitors), which were filtered based upon chemical stability and redundancy, and 31 compounds were then tested experimentally (Table 1; see also Table S1 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…We recently developed an in silico approach based on fold recognition methods to identify prospective new mART members from bacterial genomes (13). These newly discovered toxins can now be exploited as targets in the development of new antivirulence therapeutics for treating bacterial diseases and infections (9,29).Here, we focus on two DT-group mARTs targeting elongation factor 2-ExoA, a well-characterized factor produced by P. aeruginosa, and cholix, a new mART toxin recently identified with our in silico approach from V. cholerae (16)-which, along with diphtheria toxin, show nearly identical enzyme activities and inhibitor specificities (2,16,31,35,36). Using the 1.25-Å cocrystal structure of cholix toxin with PJ34 [N-(6-oxo-5,6-dihydrophenanthridin-2-yl)-(N,N-dimethylamino)acet-* Corresponding author.…”
mentioning
confidence: 99%
See 1 more Smart Citation